Floral characteristics in five landraces accessions of pumpkin (Cucurbita argyrosperma) related to the attraction of insect visitors - Balam-Pech, Maria Luisa; Ballina-Gómez, Horacio Salomón; Medina-Dzul, Kati; Ruiz-Sánchez, Esau; González-Moreno, Alejandra (Revista Colombiana de Entomología, 2023)
Pollination is extremely important for agriculture, with insects being the main pollinators. Plants have developed attraction strategies in their flowers to ensure visits from pollinators; therefore, knowing the floral characteristics that influence visits to crops could lead to improvements in yield. The floral attributes of five landraces accessions of pumpkin (Cucurbita argyrosperma) were compared: RRS004, RRS006, RRS005, RRS008 and RRS010. The experiment was carried out in a family orchard in Baca, Yucatan, Mexico. Evaluations were carried out in the period of maximum flowering, the size and area of the corolla, the height of the flower, floral display, volume and concentration of sugar in nectar, pollen production and its viability were recorded; and also, floral visitors. The results showed that there are differences in terms of floral traits between evaluated accessions, as well as the pollen and nectar floral area was associated with floral visitors. Similarly, a greater number of illegitimate visits was observed compared to legitimate visits, of which all were identified as chrysomelids (Acalymma sp.), bees (Partamona sp.), drosophilids (Drosophila sp.), thrips (Frankliniella sp.), ants (Solenopsis sp.) and wasps (Polybia sp.). Our study shows that the variation recorded in floral traits between accessions impacts the attraction of visiting insects, which demonstrates an important intraspecific variation in Cucurbita sp.